The role of counterion and concentration on the thermal behavior and structure of dioctadecyldimethylammonium bromide and chloride in water - Feitosa, Eloi [UNESP]; Adati, Renata D.; Karlsson, Göran (Elsevier, 2023)
Cationic dioctadecyldimethylammonium bromide and chloride (DODAB and DODAC) lipids assemble in water as unilamellar vesicles or more complex bilayer structures depending on the lipid concentration, counter-ion, solvent characteristics, etc. By using differential scanning calorimetry (DSC) and cryogenic transmission electron microscopy (cryo-TEM) techniques we investigated the structural and thermal properties of these two widely investigated molecules at 1–20 mM in water. Changes in the DSC thermogram profile indicate that DODAB bilayers undergo more structural changes than DODAC, while Cryo-TEM micrographs show that, in this range of concentration, DODAB assembles as more complex bilayer structures than DODAC, which assemble predominantly as unilamellar vesicles. These findings thus indicate that DODAC is preferable to DODAB at 1–20 mM for the preparation of unilamellar vesicles.
Keywords: Cationic vesicles; Cryo-TEM; Differential scanning calorimetry; DODAB; DODAC; Thermal behavior